Attachment style and romantic involvement with host nationals influence migrants’ acculturation and adjustment - Marshall T; Lao CH (Elsevier, 2024)
Many migrants experience cultural transitions alongside a romantic partner, yet relatively few studies have examined the relationship context of acculturation and adjustment. The primary goal of the present study was to examine whether partners’ anxious and avoidant attachment – fearing abandonment or closeness in relationships, respectively – predicted their acculturation orientations and sociocultural, psychological, and relational adjustment. A secondary goal was to examine whether being romantically involved with a host national eased the process of acculturation. Toward this end, we collected dyadic daily diary data over a 14-day period from 146 couples (N = 292), of whom at least one partner was a recent migrant to the UK. We found that when migrants were higher in avoidant attachment, they – and their partners – reported the poorest acculturative outcomes: lower mainstream British identification and heritage culture identification, and lower sociocultural, psychological, and relational adjustment. When migrants were higher in attachment anxiety, they reported poorer psychological, sociocultural, and relational adjustment; when their partners were higher in anxiety, migrants reported worse outcomes across the board. Furthermore, migrants with a British partner reported greater mainstream British identification and sociocultural adjustment compared to migrants without a British partner. A follow-up 7.5 years later found that migrants who were higher in attachment anxiety and did not have a British partner at Time 1 were more likely to have left the UK by Time 2. Based on these findings, we encourage researchers, clinicians, and policy-makers to take migrants’ relationship context into account to better understand their acculturation and adjustment.
Keywords: Acculturation; Adjustment; Romantic relationship; Attachment; Intercultural; UK